Medical students' attitudes and perceptions towards the effectiveness of mobile learning: A comparative information-need perspective. (March 2021) - Zhang, Xin; Lo, Patrick; So, Stuart; Chiu, Dickson K.W.; Leung, Tin Nok; Ho, Kevin K.W.; Stark, Andrew
The rapid development of information and communication technologies has revolutionized the lifestyles and learning practices of the younger population worldwide. Various new mobile platforms and forms of social media have been so pervasive and influential in the world of higher education that they have contributed much to the training of the next generation of medical professionals. As such, the current study aimed to compare the adoption of mobile learning amongst three groups of medical science students at the University of Hong Kong – namely, students majoring in Clinical Science, Chinese Medicine and Nursing. For this study, the authors used a questionnaire survey to collect a total of 150 responses. The data was analysed using descriptive statistics, Pearson's correlation test and multiple regression analysis. The results from the study revealed that the students in the three different medical majors at the University of Hong Kong engaged with their mobile devices at slightly different levels. Although a few significant differences were found, Clinical Science students tended to have more diverse information needs and use their mobile devices for a variety of learning-related activities. In comparison, Chinese Medicine students indicated that they were less active users of mobile devices in terms of both learning and non-learning activities.